2013
DOI: 10.1021/tx400207q
|View full text |Cite
|
Sign up to set email alerts
|

Chlorinated Biphenyl Quinones and Phenyl-2,5-benzoquinone Differentially Modify the Catalytic Activity of Human Hydroxysteroid Sulfotransferase hSULT2A1

Abstract: Human hydroxysteroid sulfotransferase (hSULT2A1) catalyzes the sulfation of a broad range of environmental chemicals, drugs, and other xenobiotics in addition to endogenous compounds that include hydroxysteroids and bile acids. Polychlorinated biphenyls (PCBs) are persistent environmental contaminants, and oxidized metabolites of PCBs may play significant roles in the etiology of their adverse health effects. Quinones derived from oxidative metabolism of PCBs (PCB-quinones) react with nucleophilic sites in pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
2
1

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 71 publications
1
12
0
Order By: Relevance
“…superoxide anion radical, hydrogen peroxide, and hydroxyl radical) and the PCB quinone (Song et al, 2008a, Song et al, 2008b). In addition to the potential for generation of toxic oxygen species, the metabolic pathways of PCBs may include the formation of electrophilic PCB arene oxides and quinones that may bind to nucleophilic sites on cellular macromolecules (Robertson and Gupta, 2000, Lin et al, 2000, Qin et al, 2013, Wangpradit et al, 2009, James, 2001). In fact, a large number of in vitro studies have demonstrated adduct formation of PCBs and their metabolites, in particular PCB quinones, to proteins, RNA, DNA or lipids (Robertson and Gupta, 2000, Morck et al, 2002, Ludewig, 2001, Klasson Wehler et al, 1989, Klasson Wehler et al, 1993, Zhao et al, 2004).…”
Section: Pcb Metabolism and Relevant Classes Of Pcb Metabolitesmentioning
confidence: 99%
“…superoxide anion radical, hydrogen peroxide, and hydroxyl radical) and the PCB quinone (Song et al, 2008a, Song et al, 2008b). In addition to the potential for generation of toxic oxygen species, the metabolic pathways of PCBs may include the formation of electrophilic PCB arene oxides and quinones that may bind to nucleophilic sites on cellular macromolecules (Robertson and Gupta, 2000, Lin et al, 2000, Qin et al, 2013, Wangpradit et al, 2009, James, 2001). In fact, a large number of in vitro studies have demonstrated adduct formation of PCBs and their metabolites, in particular PCB quinones, to proteins, RNA, DNA or lipids (Robertson and Gupta, 2000, Morck et al, 2002, Ludewig, 2001, Klasson Wehler et al, 1989, Klasson Wehler et al, 1993, Zhao et al, 2004).…”
Section: Pcb Metabolism and Relevant Classes Of Pcb Metabolitesmentioning
confidence: 99%
“…Thiol binding of PCB quinone metabolites has been found in glutathione and topoisomerase II, which caused a decrease of topoisomerase II activity (Srinivasan et al 2002). The covalent binding of different PCB quinones decreased the catalytic activity of human hydroxysteroid sulfotransferase hSULT2A1 (Qin et al 2013a). Using radioactive compounds, PCB3 and PCB77 were found covalently bound to nuclear proteins in liver in vivo (Pereg et al 2001) and lipids in vivo (Morck et al 2002).…”
Section: Introductionmentioning
confidence: 99%
“…37) are capable of reacting with nucleophilic sites of either DNA or proteins and can participate in some redox processes, generating ROS. However, in a study with human hydroxysteroid transferase, an enzyme responsible for the detoxification of an organism through catalytic sulfonation of both endogenous and exogenous agents, the compounds increased, rather than inhibited, enzymatic activity (Qin et al, 2013).…”
Section: Toxicology Of Quinoid Systemsmentioning
confidence: 99%